1971
DOI: 10.3171/jns.1971.34.5.0603
|View full text |Cite
|
Sign up to set email alerts
|

The pathological findings in fatal craniospinal injuries

Abstract: ✓ A series of 50 fatal cases of craniospinal injury were reviewed with particular attention to the pathological findings at the craniospinal junction. There was marked tendency for the spinal cord to be damaged in the upper cervical segments, whereas disc injuries predominated in lower cervical segments. The vertebral artery was rarely involved. The lateral ligamentous structures were often damaged, while the transverse ligaments of the odontoid were spared. Rupture of muscles was rare, although hemorrhage int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
4

Year Published

1977
1977
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(42 citation statements)
references
References 15 publications
0
38
0
4
Order By: Relevance
“…C1-C2 dissociation occurs with complete ligament lesion [1,5]. It is possible to speculate that the lesion occurred at the moment of the trauma, well before the traction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…C1-C2 dissociation occurs with complete ligament lesion [1,5]. It is possible to speculate that the lesion occurred at the moment of the trauma, well before the traction.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these ligaments involved the atlantoaxial region [5]. In a postmortem study of 14 patients who presented atlantoaxial displacement, Adams [1] identified three patients with complete rupture of the atlantoaxial ligament and of the tectorial membrane and lesion of atlantoaxial capsulae associated with type II odontoid fracture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Davis et al reported five cases of disruption of the AO joint in postmortem radiographic studies of the head and spine among 50 consecutive deaths from acute trauma. 17 In the majority of the cases from these series, the injury was immediately fatal. Autopsy evaluation after such injuries has demonstrated direct mechanical injury of the lower brainstem and upper cervical spinal cord, usually consisting of transection of the cord, cord laceration with incomplete tear of the spinal cord, or spinal cord contusion.…”
Section: Incidence Mechanism and Consequences Of Atlantooccipital DImentioning
confidence: 99%